Antifouling Zwitterionic Nanofibrous Wound Dressing for Long-Lasting Antibacterial Photodynamic Therapy - Chang, Wen-Yen; Chen, Ching-Yi (ACS omega, 2023)
Nanofibrous mats as a wound dressing have received great attention in recent year. The development of biocompatible dressings with antibiofouling capability and long-lasting antibacterial properties is important but challenging. Antibacterial photodynamic therapy (aPDT) effectively eliminates pathogens via a photodynamic process that can circumvent the emergence of antibiotic-resistant pathogens. In this study, we integrated the zwitterionic materials (2-methacryloyloxyethyl phosphorylcholine (MPC) moiety) and aPDT photosensitizer, methylene blue (MB), to fabricate a long-lasting antibacterial nanofibrous mat using electrospinning technology. The prepared nanofibers possessed an appropriate water absorption and retention ability, superior cytocompatibility, and antibiofouling ability against both proteins and L929 cell adhesion. MB-loaded nanofibrous mats have exhibited superior aPDT against Gram-positive Staphylococcus aureus compared to Gram-negative Escherichia coli under moderate irradiation (100 W m–2) due to the presence of an extra outer membrane of Gram-negative bacteria serving as a protective barrier. In vitro release study demonstrated that the nanofibrous mat had a long-lasting drug release profile, which can efficiently suppress bacterial growth via aPDT. The antibacterial ability of the MB-loaded nanofibrous mat was commensurate or slightly inferior to antibiotics such as tetracycline and kanamycin, suggesting that it has the potential to be used as an antibiotic alternative. Overall, this zwitterionic nanofibrous mat with long-lasting aPDT function and nonadherent properties has potential as a promising antibacterial wound dressing.